Storytelling and the sciences of mind - Herman, David, 1962- (The MIT Press, 2013)
"With Storytelling and the Science of Mind, David Herman proposes a cross-fertilization between the study of narrative and research on intelligent behavior. This cross-fertilization goes beyond the simple importing of ideas from the sciences of mind into scholarship on narrative and instead aims for convergence between work in narrative studies and research in the cognitive sciences. The book as a whole centers on two questions: How do people make sense of stories? And: How do people use stories to make sense of the world? Examining narratives from different periods and across multiple media and genres, Herman shows how traditions of narrative research can help shape ways of formulating and addressing questions about intelligent activity, and vice versa."